Motivational condition in educational evaluation - Acosta Muñoz, Julio Fernando; Cifuentes Mendivelso, Rossy Rossy (Universidad Pedagógica y Tecnológica de Colombia, 2012)
This is a reflection article, methodologically based on research into and theoretical and conceptual review of the motivational condition in educational evaluation. At the same time, some inquiries about the motivational problems in this education process are made. The objective is to examine what the motivational condition within the process ofeducational evaluation is. On the one hand, educational evaluation is a tool that attests to the knowledge, on the other hand, however, it prevents students from strengthening their interest both in the participation in the specific testing activity and in their learning, since it lays emphasis on extrinsic factors, such as grade, which make students lose and distort their intrinsic motivation to learn. Therefore, the evaluation proposal arisen from the construct of motivation is thought to generate in students positive sensations standing even after goals are obtained. Likewise, it must promote liveliness, integration and psychological health, in order to get students to fulfill their needs and obtain psychological welfare in the classroom.